Vzpostavitev sistema državnih topografskih baz in kart v merilih 1:50000 in 1:25000 - Petrovič, Dušan (Geodetski vestnik, 1998)
AQ national topographic map at 1:5000 scale (DTK 50) will be the next systematic topographic map in Slovenia following the national topographic map at 1:25000 scale (DTK 25). The Surveying and Mapping Authority of the Republico f Slovenia is preparing a project for production of this map especially for the needs of the Slovenian Army, in co-operation with the Institute of Geodesy and Photogrammetry FCEG. New methodological solutions, recent computer-aided technology and certain changes in content and design will represent major changes in comparison with DTK 25. Together with the DTK 50 project and two test sheets, the foundations for the second issue of DTK 25 and progressive re-establishment of the TOPO 25 topographic database will also be prepared. The project will be completed in the first half of 1999, when production of the new map will begin
Keywords: geodezija; Slovenija; topografija; topografske baze; topografske karte